2019
DOI: 10.2337/db19-2130-p
|View full text |Cite
|
Sign up to set email alerts
|

2130-P: Imeglimin Modulated ER Stress to Prevent ß-Cell Apoptosis Induced by High Glucose or Thapsigargin

Abstract: Imeglimin, a tetrahydrotriazine anti-hyperglycemic agent, is thought to have effects on mitochondrial function of the liver, skeletal muscle, and pancreatic β-cells. However, the molecular mechanisms of imeglimin action have been still unclear. Treatment of mouse islets with 1.0 mM imeglimin significantly increased insulin release in response to glucose (2.1-fold, p<0.01 at 11.1 mM glucose; 1.9-fold, p<0.05 at 16.7 mM glucose, compared to 3.9 mM glucose). Treatment with a combination of liragluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Moreover, the molecule was shown to prevent the death of cultured rat β cells and INS‐1 cells when exposed to pro‐inflammatory cytokines and high glucose, respectively 12 . Similarly, a preliminary report revealed that imeglimin prevents β‐cell apoptosis induced by high glucose in both rat and human isolated islets 31 . These findings and the current results beg the following question: What mechanism(s) may underlie the ability of imeglimin to reduce β‐cell apoptosis and preserve mass?…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the molecule was shown to prevent the death of cultured rat β cells and INS‐1 cells when exposed to pro‐inflammatory cytokines and high glucose, respectively 12 . Similarly, a preliminary report revealed that imeglimin prevents β‐cell apoptosis induced by high glucose in both rat and human isolated islets 31 . These findings and the current results beg the following question: What mechanism(s) may underlie the ability of imeglimin to reduce β‐cell apoptosis and preserve mass?…”
Section: Discussionmentioning
confidence: 92%
“…In addition to direct effects to amplify GSIS, previous in vitro studies performed with isolated human or rat islets or cultured rat insulinoma (INS1) cells showed a protective effect of Imeglimin to reduce cell death in response to cytokines or high glucose incubation 41,46 . These effects suggested that Imeglimin might have longer term benefits to prevent the loss of functional β‐cell mass in T2D.…”
Section: Reversal Of Pancreatic Islet β‐Cell Dysfunctionmentioning
confidence: 99%
“…They also suggested that imeglimin increases beta cell mass by inhibitory impacts on permeability transition pores (PTP) of mitochondria [25]. There is a growing evidence confirming the protecting roles of imeglimin on beta cells [9,26]. The above mentioned evidence suggests that imeglimin improves glucose homeostasis partly via promoting beta-cell function.…”
Section: Imeglimin and Gluconeogenesismentioning
confidence: 98%
“…Beyond the above described metabolic effects, imeglimin can provide additional pharmacologic effects [26]. For example, it improves endoplasmic reticulum stress and in turn inhibits various downstream pathophysiologic pathways [26].…”
Section: Other Beneficial Effects Of Imeglimin In Dm and Its Complicamentioning
confidence: 99%
See 1 more Smart Citation